Kyiv’s White House wooing implodes as Zelenskyy tells the truth about Trump - Borger, Julian (The Guardian, 2025)
All America’s allies know that Trump is trapped in a disinformation bubble, but Zelenskyy said it out loud
Keywords: Donald Trump; Trump administration; US politics; Ukraine; Volodymyr Zelenskyy